Tingkatan Eksistensi dan Motivasi dalam Islam serta Relevansinya dengan Ekonomi Islam - Abbas J. Ali; Yoyo Hambali (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
Purpose – This paper seeks to shed light on Islamic perspectives on motivation and personality. It argues that original Islamic thinking in the seventh and eleventh centuries offer useful organizational insights for today’s organizations. Design/methodology/approach – This research contrasts an earlier Islamic writing on motivation and personality with contemporary humanistic theories on motivation. This study suggests that religion and spirituality can positively influence behavior and organizational performance. Findings – It shows that religion may provide a potentially useful framework within which to study the relationship between faith and work. It was documented that the Islamic profile of human existence (Mutamainna) challenges most of the prevailing management assumptions on human beings. Practical implications – Opens up a new avenue for viewing the nature of human existence and dispels the widely held belief that human beings by nature are destined to engage in destructive behavior. Originality/value – The paper provides original conceptualizations and perspectives that are of value to researchers in the fields of spirituality and international comparative management. The paper offers a new perspective on how the degree of internalization of spiritual needs influences an individual’s behavior and expectations.